THE DEVELOPMENT AND DESAIGN OF PUBLIC MEDIA FOR THE LEARNING OF TENTH GRADE HIGH SCHOOL CLASS EDUCATION - Rina Utami; Moch. Yusuf Zen; M. Iqbal Baihaqi (JOSAR (Journal of Students Academic Research), 2020)
In accordance with observations made by researchers the hypothesis that researchers get at Sutojayan SMAN and SMAN 4 Blitar schools still has constraints in the facilities and infrastructure available at school, learning there are still obstacles that are experienced in the learning process, so researchers developed PUBPIN learning media. Researchers use the R&D method with the following steps: potential problems that exist in schools namely inadequate facilities and infrastructure, observations were made at Sutojayan SMAN and SMAN 4 Blitar, PUBPIN design, PUBPIN validation, PUBPIN revision, PUBPIN trials, PUBPIN revisions, and publications. The PUBPIN learning media is validated by the media expert validator, the material expert validator, and the language expert validator and simulated to the X Grade 4 Blitar high school students. Evaluation of the feasibility of the media using a Likert scale and assessment of student responses using the Guttman scale. Based on the analysis of media expert judgment data by 90% categorized as very feasible, the material expert assessment by 87.1% is categorized as feasible, the linguist assessment by 98.3% is categorized as very feasible, and the assessment of the response of Blitar 4 SMAN students on average by 98.7% was categorized as very feasible.